On the Metaphorization of the Concept of Cloud in Selected Polish and Russian Poetic Works – A Linguistic Approach - Jolanta Kur-Kononowicz (Zeszyty Cyrylo-Metodiańskie)
The aim of the article is to describe the ways of metaphorizing the concept of cloud in selected Polish and Russian poetic works and to determine the frequency of use of a given metaphorical pattern. The monometaphoric pattern is described from a cognitive perspective. Metaphors are divided into: artifactual, anthropomorphic, zoomorphic, naturomorphic and phytomorphic. The features of the source and target domains, on the basis of which metaphorical transfer occurs, have been considered. The work concludes with the presentation of the similarities and differences in the perception of the concept of cloud in selected Polish and Russian poetic works. Original title in Polish: O metaforyzacji konceptu ‘obłok’ w wybranych polskich i rosyjskich utworach poetyckich – ujęcie lingwistyczne.